2019
DOI: 10.3390/min9110674
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Fractions of the Agricultural Soils of Southern Poland and the Assessment of the Potentially Harmful Element Mobility

Abstract: Surface samples (0–25 cm each) of agricultural soils were investigated in five Regions (voivodeships) of southern Poland. The mean Potentially Harmful Element (PHE) pseudototal content ranges were as follows (mg/kg): As 5.19–10.9, Cd 0.34–1.56, Co 1.92–6.70, Cr 9.05–25.7, Cu 8.74–69.4, Hg 0.001–0.08, Ni 3.93–19.9, Pb 20.3–183, Sb 0.80–1.42, Tl 0.04–0.17, and Zn 61.3–422. The PHE availability depended on pH, the organic carbon (Corg) content, and the pseudototal PHE content in soils. Exchangeable and acid solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…In reference, the PHE contents determined in this study were contained within the concentration ranges of cereals cultivated in Poland reported by Kabata-Pendias [5]. Because Cd, Ni, Zn, Pb, and Cu were present in bioavailable forms in the investigated soils of southern Poland [30], that might cause PHE accumulation in the analyzed cereals. The results obtained by Kan et al [75] indicated the highest Zn contents in rye, which were in line with the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…In reference, the PHE contents determined in this study were contained within the concentration ranges of cereals cultivated in Poland reported by Kabata-Pendias [5]. Because Cd, Ni, Zn, Pb, and Cu were present in bioavailable forms in the investigated soils of southern Poland [30], that might cause PHE accumulation in the analyzed cereals. The results obtained by Kan et al [75] indicated the highest Zn contents in rye, which were in line with the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…The second principal component (PC2) explained 26.0% of variance and had negative loading values for Ni and Cd, indicating a tendency of rye and oat to contain those PHEs. Moreover, the component could be correlated with easiness of Cd and Ni bioaccumulation in plants [51][52][53][54], because bioavailable concentrations of those PHEs were determined in soil [30]. The PCA ordination diagram for the first two PCs computed for PHE contents in cereals is presented in Figure S1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations